The effects of feeder design (conventional dry vs. wet-dry) in the nursery and in the finisher on growth performance of finishing pigs - S Nitikanchana; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2011)
A total of 1,296 pigs (PIC 1050 × 337; initially 36 lb) were used in a 102-d study to determine the effects of feeder type (conventional dry vs. wet-dry) on nursery and finishing pig growth performance for pigs reared under commercial conditions. In the nursery, pigs were housed in rooms with either conventional dry or wet-dry feeders. At movement to the finisher, 312 barrows and 336 gilts from a room with conventional dry feeders and an equal number of pigs from a room with wet-dry feeders were randomly selected and distributed to have a similar number of barrows and gilts in each finisher pen. At the start of the trial, pens of pigs were weighed and randomly allotted to the 2 feeder types in finishing barn to arrange the treatments as a 2 × 2 factorial with main effects of feeder type in nursery and feeder type in finisher. All pigs were fed the same corn-soybean meal diets containing 20 to 40% dried distillers grains with solubles (DDGS) during 6 dietary phases. For the finisher period (d 0 to 102), pigs fed with the conventional dry feeder during the nursery phase and wet-dry feeder during the finisher phase tended to have greater ADG (P<0.01) compared with pigs fed with the other feeder regimens. An interaction (P = 0.03) occurred between nursery and finisher feeder type for F/G. Within pigs provided feed with the conventional dry feeder in the nursery phase, pigs provided feed with the conventional dry feeder in the finisher phase had poorer (P<0.01) F/G compared with those fed with the wet-dry feeder. In contrast, for pigs provided feed with the wet-dry feeder in the nursery phase, F/G during the finisher phase was the same regardless of feeder type in the finisher phase. Pigs previously fed using a conventional dry feeder in the nursery had greater ADG and ADFI (P = 0.03, P = 0.02) compared with those on wet-dry feeder in the nursery phase regardless of the effect of feeder types in finishing period. Pigs fed with wet-dry feeders in the finisher phase had greater (P<0.01) finisher ADG and improved (P = 0.02) F/G compared with those fed with conventional dry feeders in the finishing period. Also, the final BW of finishing pigs previously fed using conventional dry feeders in the nursery was greater (P<0.01) than those previously fed on wet-dry feeders; however, pigs fed using wet-dry feeders in finisher phase had greater (P<0.01) final BW compared with those fed with conventional dry feeders. These results indicated that using dry feeder in nursery and wet-dry feeder in finisher gave the most benefit in terms of growth performance.; Swine Day, Manhattan, KS, November 17, 2011
Keywords: Swine Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-064-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1056; Swine; Conventional dry feeder; Wet-dry feeder; Finishing pig